Chronic kidney disease is characterized by "double trouble" higher pulse pressure plus night-time systolic blood pressure and more severe cardiac damage. - Massimiliano Fedecostante; Francesco Spannella; Giovanna Cola; Emma Espinosa; Paolo Dessì-Fulgheri; Riccardo Sarzani (PLoS ONE, 2014)
BACKGROUND: Hypertension plays a key role in chronic kidney disease (CKD), but CKD itself affects the blood pressure (BP) profile. The aim of this study was to assess the association of BP profile with CKD and the presence of cardiac organ damage. METHODS: We studied 1805 patients, referred to our Hypertension Centre, in whom ABPM, blood tests, and echocardiography were clinically indicated. The glomerular filtration rate was estimated (eGFR) using the MDRD equation and CKD was defined as eGFR<60 mL/min/1.73 m(2). Cardiac organ damage was evaluated by echocardiography. RESULTS: Among patients with CKD there were higher systolic blood pressure (SBP) during the night-time, greater prevalence of non-dippers (OR: 1.8) and increased pulse pressure (PP) during 24-hour period, daytime and night-time (all p<0.001). Patients with CKD had a greater LVM/h(2.7) index, and a higher prevalence of left ventricular hypertrophy and diastolic dysfunction (all p<0.001). Nocturnal SBP and PP correlated more strongly with cardiac organ damage (p<0.001). Patients with CKD had a greater Treatment Intensity Score (p<0.001) in the absence of a significantly greater BP control. CONCLUSIONS: CKD patients have an altered night-time pressure profile and higher PP that translate into a more severe cardiac organ damage. In spite of a greater intensity of treatment in most patients with CKD, BP control was similar to patients without CKD. Our findings indicate the need of a better antihypertensive therapy in CKD, better selected drugs, dosages and posology to provide optimal coverage of 24 hours and night-time BP.